Locomotor Demands in Professional Male Football Players: Differences and Variability According to Halves and Playing Positions - Akyildiz, Zeki; Yuksel, Yilmaz; Cene, Erhan; Parim, Coskun; Silva, Rui Miguel; Isik, Anil; Yildiz, Mehmet; Silva, Ana Filipa; Badicu, Georgian; Clemente, Filipe Manuel (MRE PRESS, 2022)
Background: The aims of the present study were three-fold: to (i) analyze between-position differences according to match activity; (ii) analyze within-position differences according to match halves; and (iii) test the variability of match activity according to both playing positions and match halves. Methods: This study followed an observational analytic prospective design. 21 elite football players participated in this study, where 25 league and 3 continental cup matches were analysed. The differences and consistency of all parameters in the two halves of the match were analyzed. The distances and metabolic power values of an elite football team were recorded using an optical camera technology during the observational period. Total distance (TD), walking, jogging, running and high speed running (HSR) measures were further analyzed. Results: Between-position differences for the overall locomotor measures per minute are present during both halves, except for walking intensity. Defenders (DO and midfielders (MF) showed significant within-position differences between halves for ID (DF: p = 0.000; eta(2) = 0.127; MF: p = 0.000; eta(2) = 0.168), for jogging (DF: p = 0.002; eta(2 )= 0.271, and for running (DF: p = 0.000; eta(2) = 0.067; MF: p = 0.000; eta(2) = 0.160). HSR and metabolic power (MP) had greater between-position variability differences. While, within-position differences were observed only for forwards (IV) during the 2nd half for HSR. Conclusions: The high-intensity locomotor measures produce higher between- and within-position differences between halves, and the HSR measure have higher between-position variability during the 1st half of a football match. For those reasons, coaches need to consider the variations that are present in high-intensity locomotor measures of each position to better adjust training.
Keywords: football; match activity; athletic performance; variability; SOCCER PLAYERS; PHYSICAL PERFORMANCE; INJURY RISK; PASSAGES; Public, Environmental & Occupational Health